The informal institutions and the knowledge sharing: the mediating effect of the social identity and the organizational trust - Moreno, Erendira Fierro (2016)
The aim of this scientific paper is to determine the extent to which social identity and organizational trust mediate the relationship between informal institutions and the exchange of knowledge. Based on a review of literature and relying on the theoretical perspective of new institutionalism and on the resource based-view the research hypotheses were formulated. Using a cross-sectional and with Mexican public sector organizations and through the perceptions of 252 public servants the hypotheses were tested. Multivariate analysis (SEM) was performed. The results confirm the importance of informal institutions that legitimize the performance of organizations but do not guarantee its real efficiency. However, research shows that intervening valuable resources management (social identity and organizational trust) helps to exploit opportunities and neutralize threats from the environment generating new capabilities: the exchange of knowledge.